Spatial-temporal heterogeneity of ecosystem service interactions and their social-ecological drivers: Implications for spatial planning and management - Xia, Hao; Yuan, Shaofeng; Prishchepov, Alexander V. (Resources, conservation and recycling, 2023)
•We analyzed ecosystem service (ES) interactions at diverse spatial-temporal scales.•ES synergies, trade-offs, and bundles changed over time, space, and scales.•Trade-offs prevail between food production and other ESs across time, space, and scales.•Hydrological ESs with weakened synergies were prioritized for ES management.•ES bundles enlighten spatial planning strategies at different spatial scales. Uncovering the complex interactions among ecosystem services (ESs) is a prerequisite for managing multiple ESs simultaneously. We mapped the supply of six ESs, quantified their trade-offs/synergies and bundles, determined dominant social-ecological drivers, and subsequently provided sustainable spatial planning and management strategies at both grid and sub-watershed scales. The results revealed that: (1) the patterns of ESs were spatially heterogeneous, with food production decreasing the most, by 14.86% (grid scale) and 17% (sub-watershed scale), and water supply increasing the most, by 22.46% (grid scale) and 22.57% (sub-watershed scale) from 2000 to 2020; (2) ten ES pairs presented synergies while five ES pairs related to food production showed trade-offs at both spatial scales, with three ES pairs at the grid scale and two ES pairs at the sub-watershed scale experiencing declined synergies or increased trade-offs; (3) our spatial-temporal and cross-scale analysis of ES interactions identified ES pairs with declined synergies as an additional priority in ecosystem management and determined ES bundles as a zoning basis for spatial planning at both scales. The similarities and divergences in ES interactions and their drivers at different scales require the linkage and distinct focus of spatial planning at different scales. Thus, we integrated spatial-temporal and cross-scale knowledge on ES interactions into spatial planning to underpin sustainable ecosystem management across scales.